2022
DOI: 10.1039/d2ra02183h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of phase change materials for thermal energy storage: a review

Abstract: Phase change materials (PCM) have had a significant role as thermal energy transfer fluids and nanofluids and as media for thermal energy storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…The thermal stability and reliability of PGO-CTAB/CS6(6) was confirmed by the freeze−thaw cycling test100 times. As shown in Figure 10 d, the pattern of characteristic peaks on the after-100-cycles curve almost remained, and the calculated enthalpy capacity was 98.57% as the initial value, implying the excellent stability of PGO-CTAB/CS6(6) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability and reliability of PGO-CTAB/CS6(6) was confirmed by the freeze−thaw cycling test100 times. As shown in Figure 10 d, the pattern of characteristic peaks on the after-100-cycles curve almost remained, and the calculated enthalpy capacity was 98.57% as the initial value, implying the excellent stability of PGO-CTAB/CS6(6) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…145,146 Molecular dynamics (MD) simulation simulates the motion trajectory of atoms or molecules, elucidating the thermodynamic properties and dynamic behavior of materials. 147,148 These techniques assist researchers in predicting material performance, stability, and interactions, thereby guiding material design and optimization. However, this approach incurs substantial computational costs and time.…”
Section: Machine Learning-based Performance Predictionmentioning
confidence: 99%
“…Molecular dynamic studies have shown that the thermal conductivity of paraffins is influenced by the orientation of the molecules in the crystal lattice. 17 The alkane crystal lattice consists of long straight chains of molecules in trans conformation with the long axis aligned in parallel, 18 but it is not well-known if it also affects the thermal properties of crystals formed from molten paraffin. The thermal conductivity is relatively low in the direction orthogonal to the alkane chains due to the low packing density in that plane and to the weak van der Waals force between the methylene groups of adjacent alkane molecules.…”
Section: Introductionmentioning
confidence: 99%